ANALISIS PENERAPAN P5 DALAM KURIKULUM MERDEKA TERHADAP PEMBELAJARAN MATEMATIKA KELAS IV DI SD NEGERI 55 PRABUMULIH - Rahma Tunisia; Marhamah; Arief Kuswidyanarko (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to describe the teacher’s strategies in implementing the Strengthening Pancasila Student Profile Project (P5) in fourth-grade mathematics learning at SDN 55 Prabumulih. The research employed a descriptive qualitative approach with a phenomenological design. Data were collected through observation, interviews, and documentation, validated using triangulation, and analyzed through data reduction and data presentation to obtain an overview of the instructional strategies used by the teacher. The results of the study show that the teacher applied various strategies aligned with the six dimensions of P5. In the dimension of faith and noble character, the teacher linked the material to religious values and fostered habits of honesty and discipline. In the dimension of global diversity, the teacher encouraged students to appreciate differences through group discussions. In the dimension of cooperation, the teacher assigned roles and facilitated student collaboration. In the dimension of independence, the teacher provided independent tasks and opportunities for students to try solving problems individually. In the dimension of critical reasoning, the teacher provided problems that could be solved using various methods and asked students to explain the reasoning behind their chosen strategies. In the dimension of creativity, the teacher allowed students to discover unique ways to solve problems and engage in simple projects. Overall, the teacher’s strategies successfully integrated P5 into mathematics learning and supported the development of students’ character and thinking skills